2023
DOI: 10.1111/asj.13813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2,5‐dimethyl‐4‐hydroxy‐3(2H)‐furanone, a volatile odor compound generated by the Maillard reaction, in cooked meat of various animal species and parts

Abstract: Abstract2,5‐Dimethyl‐4‐hydroxy‐3(2H)‐furanone (DMHF), a compound having a sweet caramel‐like odor, is one of the major compounds generated by the Maillard reaction. DMHF could affect the palatability of cooked and processed foods such as meat, while its inhalation induces several physiological functions. However, basic findings of DMHF generation in meat remain unclear. In this study, we compared the amount of DMHF in cooked meat of various animal meat (Japanese black cattle beef, Australian beef, pork, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Lower content of sugars and sweet‐tasting FAA in high IMF% beef may have reduced the sensory perception of sweet butter‐like flavor. Furthermore, Yokoyama et al (2023) reported that the generation of DMHF, which has caramel‐like sweet aroma, in cooked beef was positively correlated with glucose content. Considering our chemical analysis and these results, the optimal balance of the sweet aroma compounds derived via Maillard reaction and lipid oxidation and sweet‐tasting compounds to enhance sweet flavor perception possibly caused the sweet flavor peak at approximately 40%–50% of IMF.…”
Section: Discussionmentioning
confidence: 99%
“…Lower content of sugars and sweet‐tasting FAA in high IMF% beef may have reduced the sensory perception of sweet butter‐like flavor. Furthermore, Yokoyama et al (2023) reported that the generation of DMHF, which has caramel‐like sweet aroma, in cooked beef was positively correlated with glucose content. Considering our chemical analysis and these results, the optimal balance of the sweet aroma compounds derived via Maillard reaction and lipid oxidation and sweet‐tasting compounds to enhance sweet flavor perception possibly caused the sweet flavor peak at approximately 40%–50% of IMF.…”
Section: Discussionmentioning
confidence: 99%
“…During the Maillard reaction, a variety of volatile flavor compounds are formed. Although the flavor strength, especially the overall concentration of flavor substances, is influenced by thermal processing conditions, temperature, pH, water content, and others, the sensory profile is controlled by the type of amino substrate, such as amino acids or small peptides . Similar to Cys, GSH is also thought to be one of the precursors of a meaty aroma .…”
Section: Introductionmentioning
confidence: 99%